Theropod Tridactyl Tracks Across the Triassic–Jurassic Boundary in Southern Africa: Implications for Pedal Morphology Evolution - Abrahams, Miengah; Bordy, Emese M.; Knoll, Fabien; Farlow, James O. (Frontiers in Ecology and Evolution, 2022)
The end-Triassic mass extinction events mark a pivotal period in archosaur history, and have been proposed to contribute to the rise and dominance of dinosaurs throughout the Mesozoic. In southern Africa, the Triassic–Jurassic boundary is contained within the richly fossiliferous fluvio-lacustrine-aeolian deposits of the upper Stormberg Group in the main Karoo Basin. Due to an absence of high-resolution radioisotopic age constraints, the exact placement of the boundary remains difficult. The Stormberg Group theropod osteological record is limited to scarce, fragmentary material; therefore, the abundant Norian–Pliensbachian tridactyl tracks attributed to theropods are vital for unravelling theropod dinosaur evolutionary trends in southwestern Gondwana. This study considers over 200 upper Stormberg Group tridactyl tracks assigned to the Kayentapus-Grallator-Anchisauripus-Eubrontes (K-GAE) plexus, to quantify their morphological variation across a time span of 35 million years. Our findings show that within the upper Stormberg Group, and across the Triassic–Jurassic boundary, the younger tracks become larger, have a decreased mesaxony and a reduced digit III projection. This reduced emphasis of the medial digit is also observed across the K-GAE plexus, and for the individual ichnotaxa across time in the main Karoo Basin e.g., Eubrontes tracks become less mesaxonic and have a reduced digit III projection higher up in the stratigraphy. This suggests that these morphological trends are not simply linked to size but may reflect a change in autopod morphology through time, which has implications for pedal functionality. Furthermore, being morphologically distinct from contemporaneous North American K-GAE tracks (e.g., reduced elongation and mesaxony, no correlation between digit divarication angles and size), these southern African footprints warrant further investigation.